Interpretacja wystroju grobowców północnojordańskich w świetle symboliki okresu rzymskiego - Skupinska-Lovset, Ilona (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
The necropolis in Qweilbeh-Abila, Jordan, has been explored since 1969. The results were published by French scholars in two volumes of high value. Both the topography of the tombs and their inventory show similarities to these of Skythopolis, the westernmost town of the Syrian Decapolis. In this article painted decoration of one of the tombs (tomb QI), called the tomb of Loukianos, is considered. In its side room a series of four pictures showing a young woman in varying poses, supplemented by two pictures with therio-vegetal motives were placed on the walls. This series has been interpreted by the French scholar as belonging in a Christian context and was dated to the Late Antique period. This author, pointing to dress and material context interprets the pictures as connected with a Pagan eschatology, especially vivid in the Orient in the Hadrianic period. She interprets the pictures as showing an educated and well-adjusted girl from a well-to-do family in scenes characteristic of the life of a girl of her standing: reading, playing music, dancing. A second century date is proposed for the painted decoration, pointing to the provincialism of the style.